The Modern State After Kant A Materialist Approach - Dariush M. Doust (European Scientific Journal, ESJ, 2023)
This article proposes an encounter between Kant’s political doctrine and Marx’s materialist method. The primary aim of this materialist critique of Kant is to discern the structure that determines the specific mode of functioning of the modern state. The article starts with Kant’s conception of freedom and law and relates these concepts to his theory of history. In the first and second sections, Kant’s political doctrine is subject to a critical reversal that more closely engages with Marx’s critical materialist approach. The article then concludes upon a new, topological approach to the ternary structure involving the intersection of three “rings”—capitalist circulation, the state in its legal effective reality, and measured labor forces in production.